SES health gradients during the epidemiological transition: The case of China - Xiaoyan Lei; Nina Yin; Yaohui Zhao (Institute for the Study of Labor (IZA), 2010)
The epidemiological transition, which has already passed the developed world, is still progressing in many developing countries. A particular problem associated with this transition is the under-diagnosis and lack of treatment of chronic diseases, and these may exhibit SES gradients and exacerbate social inequality. Using hypertension as an example and data from China (CHNS), we find that the prevalence of hypertension in China is already close to levels in developed countries, under-diagnosis is pervasive, treatment is rare, and failure to control is widespread. Consistent with the literature, we find no income and education gradients in the prevalence of hypertension. However, there are strong education gradients in diagnosis and treatment in urban areas. The income gradients in all aspects of hypertension are relatively weak and sometimes nonexistent. Interestingly, we find that access to health care does not contribute to the diagnosis of hypertension, nor does it aid much in the treatment and control of hypertension. Our results suggest that the epidemiological transition has indeed occurred, but both the Chinese public and its health care system are ill-prepared. There is an urgent need to educate the public on chronic illnesses, and to raise the quality of health care so that patients receive proper diagnoses and guidance on how to treat and control those chronic illnesses.
Keywords: I10; 330; Epidemiological transition; under-diagnosis; SES health gradients; Gesundheitsversorgung; Demographischer Übergang; Bildungsniveau; Herzkrankheit; China